Study of the elemental composition of rhizome with roots of horse sorrell - Oproshanska, Tetyana; Khvorost, Olha (Annals of Mechnikov's Institute, 2024)
Introduction. Macro- and microelements are one of the most important groups of biologically active substances, the deficiency of which in the body leads to disruption of the immune system, hematopoietic system, and metabolism. Horse sorrel is an invasive plant that is widespread and does not require special growing conditions. The underground organs of the plant are used in traditional medicine and they contain tannins, anthracene derivatives, organic acids, polyphenolic compounds, anthocyanins, carbohydrates. It is known that the presence of such elements as potassium, sodium, chlorine, nitrogen and phosphorus in the soil effects on the growth of the horse sorrel, but we did not find modern studies on the study of the elemental composition of plant raw materials that grow wild in soils without fertilizers. Therefore, the study of the elemental composition of rhizomes with roots of horse sorrel, which grows in natural conditions in different regions of Ukraine, is relevant. The purpose of the work is to study the elemental composition of rhizomes with roots of horse sorrel, which grows wild in different regions of Ukraine. Materials and methods. It was used rhizomes with the roots of horse sorrel for the research. Elemental analysis was carried out using the atomic emission spectrographic method with photographic registration on the DFS-8 device. Results and discussion. It was determined the quantitative content of 15 elements: 5 macro- and 10 micro-elements in five series of the wild plant raw material of horse sorrel. It is observed the following pattern of accumulation of macroelements in all series: K>Ca>Na>Mg>P. The highest content is characteristic of K and Ca. The P content in all series was the lowest. The following regularity is observed in the range of identified microelements for 5 series of plant raw materials: Si> Fe> Al> Mn. Content of Mo and Pb were in minor amounts in all series of plant raw materials. The amount of as is beyond the sensitivity of the device. The content of toxic elements is within the limits stipulated by the requirements of SPhU 2.0. Conclusions. It was studied the elemental composition of 5 series of rhizomes with the roots of wild species of horse sorrel which grows in different regions of Ukraine. The quantitative content of 15 elements was determined: 5 – macro- and 10 microelements. It was established that the content of macroelements K and Ca and microelement Si dominates in 5 series. The content of Pb was <0.03mg/100g, and As is beyond the sensitivity of the device. The obtained results will be taken into account when a tincture from the rhizomes with the roots of horse sorrel be create. Keywords: horse sorrel, rhizomes with the roots, elemental composition